Perceived stress among Malaysian railway workers - Radman Al-Dubai, Sami Abdo; Ganasegeran, Kurubaran; Elkalmi, Ramadan Mohamed Mahmod; Alshakka, Mohammed; Ghanem, Nizar (Universiti Sains Malaysia, 2016)
Background: Stress is a common work-related problem worldwide. Railway workers are predominantly stressed due to their rigid protocols and limited rest opportunities. This study aimed to determine the level of, and factors associated with, stress among railway workers in Malaysia. Methods: A cross-sectional study was conducted among all 729 railway workers employed at Keretapi Tanah Melayu Berhad (KTMB) in eight states in Malaysia via a postal survey. The selfadministered questionnaire consisted of socio-demographic characteristics and the validated Malay version of Perceived Stress Scale-10 (PSS-10). Response rate was 70.4% (513/729). Results: Mean (SD) age of workers was 41.4 (10.7), with the majority aged 30 years or older (79.3%). Mean (SD) perceived stress was 18.8 (4.3). In multiple linear regression analysis, the significant predictors of high stress were high school versus tertiary education (β = 0.10, 95% CI 0.11, 1.73, P = 0.027) and being a white collar worker versus blue collar (β = 0.113, 95% CI 0.10, 1.74, P = 0.010). Conclusions: Education level and type of work were significantly associated with perceived stress among railway workers in this study.